Rhetoric and region: local determinants of literary expression (2013)
Writings on natural disasters reflect tragic experiences of peoples and the nostalgic cravings after it. This study examines the portrayal of earthquakes, storms and tsunamis as a national concern in Japanese literature. The portrayal of the theme, which has remained a topical issue, is psychological, and sociological. The portrait of personal and communal loss is a reflection of the perspectives and survival strategies that emerge after such disasters occur. This study examines two narrative accounts and a poetry piece written to capture the magnitude and effect of the earthquakes at different periods in Japan. The study examines these writings vis-a-vis media accounts of the recent 2011 Tohoku earthquake and tsunami, and the Fukushima Daichi nuclear disaster.